Modelling stakeholders’ preferences to pinpoint conflicts in the planning of transboundary protected areas - Castro-Pardo, Mónica de; Pérez-Rodríguez, Fernando; Martín Martín, José María; Azevedo, Joao C. (Land Use Police, 2019)
In this paper, we propose a sequentially participative model for planning in transboundary protected areas based on the Analytical Hierarchy Process, Goal Programming and Monte Carlo simulation. The model was developed with two scenarios: one determinist and another with simulations that provide a multi-level ranking of the most relevant goals according stakeholders’ preferences to establish priorities in the planning of protected areas. Moreover, the proposed methodology is capable of identifying conflicts, providing a comparison between the most likely priorities and the most consistent group priorities associated with each planning goal. The model was tested in a Portuguese-Spanish Reserve called Meseta Ibérica and it permitted the identification of the highest conflicts in conservation, agroforestry, local development, fire prevention, wildlife conservation and certification of local products. Moreover, it found strong intercountry conflicts related to development and planning goals associated with governance at the most specific level.
Keywords: multi-level planning; sequential Monte Carlo simulation; AHP; group decision-making; governance; Scopus; JCR